2017
DOI: 10.1002/jso.24691
|View full text |Cite
|
Sign up to set email alerts
|

A quantified risk‐scoring system and rating model for postsurgical gastroparesis syndrome in gastric cancer patients

Abstract: Visceral obesity defined by VFA effectively predicted PGS. Our scoring system may be a reliable instrument for identifying patients most at risk of PGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…The etiology of postsurgical gastroparesis syndrome (PGS) was diverse. Recent studies identified several risk factors for PGS, such as patient BMI ≥ 25 kg/m 2 , age ≥ 65 years, B-II reconstruction and the like [33, 35]. In the present study, PGS occurred in 16 patients in total.…”
Section: Discussionmentioning
confidence: 48%
“…The etiology of postsurgical gastroparesis syndrome (PGS) was diverse. Recent studies identified several risk factors for PGS, such as patient BMI ≥ 25 kg/m 2 , age ≥ 65 years, B-II reconstruction and the like [33, 35]. In the present study, PGS occurred in 16 patients in total.…”
Section: Discussionmentioning
confidence: 48%
“…Diagnosis of PGS. PGS was diagnosed according to the following criteria, which were reported in our previous research [2]: ≥1 medical examinations confirming the absence of mechanical gastric outflow obstruction; stomach drainage volume > 800 mL/day sustained for >10 days; no obvious abnormality in fluid-electrolyte balance; no underlying disease, such as hypothyroidism or choroiditis, which may cause PGS; and no current treatment with any medications that may affect smooth muscle contraction.…”
Section: Methodsmentioning
confidence: 99%
“…Postsurgical gastroparesis syndrome (PGS) presents with symptoms suggesting gastric retention, including delayed gastric emptying, in the absence of mechanical obstruction [1]. Its prevalence following gastrectomy has been reported to be 0.4% to 5.0% [2]. PGS imposes significant social and economic burdens, including increased hospitalization time and healthcare costs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgical Gp may also be seen after other surgeries, including esophagectomy (12%), distal gastrectomy with Roux-en-Y reconstruction (9%), lung transplantation (6%), paraesophageal hernia repair (4.4%) and fundoplication (3.8%) [78][79][80]. The presence of visceral obesity predicts the development of postsurgical Gp in patients undergoing distal gastrectomy for gastric cancer [81]. Postsurgical delay in gastric emptying may result in a higher severity of gastrointestinal symptoms.…”
Section: Role Of Gastric Emptying In Symptoms Of Gastroparesismentioning
confidence: 99%